Epidemiological aspects of leprosy in Juazeiro-BA, from 2002 to 2012 - Maria Eduarda Gomes da Cruz Silva; Carlos Dornels Freire de Souza; Susanne Pinheiro Costa e Silva; Flávia Monteiro da Costa; Rodrigo Feliciano do Carmo (Sociedade Brasileira de Dermatologia, 2015)
Abstract: BACKGROUND: Leprosy is an infectious disease caused by Mycobacterium leprae, able to infect large numbers of people. This work is relevant to Juazeiro-BA, a hyper-endemic area for leprosy, since unravel the behavior of the disease in the area, may suggest the decision making for sectors of surveillance, establishing strategies, organizing and evaluating programs and services. OBJECTIVES: To analyze the epidemiology of leprosy in Juazeiro-BA, from 2002 to 2012. METHODS: A descriptive, cross-sectional study was conducted based in data of the Diseases Notification System, assigned by the service of Epidemiology from Juazeiro-BA, between 2002 and 2012. RESULTS: 1,916 new cases of leprosy were detected between 2002 and 2012, of which 921 (48.07%) represented male sex, 995 (51.93%) female, and there was a reduction in the incidence rate of leprosy per 100,000 inhabitants. Most carriers were brown individuals, with low levels of education, living in the urban area, being more prevalent in the economically active age group. Through statistical analysis we found that there are more chances of developing sequelae among men, and multibacillary individuals older than 45 years. CONCLUSIONS: The work serves to direct efforts to control this disease, and highlights the importance of active search for new cases to achieve an early diagnosis, reducing the number of sequels and allowing breaking the chain of disease transmission.